From “Quick Wins” to Smart Governance: Building Dynamic Managerial Capabilities in Jambi City - Mar Atun Saadah; Tiyara, Agus; Try Syeftiani; Feny Tialonawarmi; Hendriyaldi; Istiqomah Malinda S.B (Department of Government Affairs and Administration, Universitas Muhammadiyah Yogyakarta, 2025)
The smart city initiative in Jambi City exemplifies the opportunities and challenges of digital transformation in local governance. This study develops a framework for smart governance transformation in Jambi City, focusing on two critical components: the dynamic managerial capabilities of municipal staff and aligning digital application architecture with Smart Governance (SG) principles. Using a mixed-methods approach, we quantitatively assessed the influence of managerial capabilities and technology adoption factors on smart governance outcomes. We employed the Technology Adoption Model (TAM) and the Technology–Organization–Environment (TOE) framework to guide this assessment. We then qualitatively validated the results through interviews, focus group discussions, and document analysis. The study found that dynamic managerial capabilities have a stronger impact on smart governance outcomes than technology factors alone. Stakeholders who embraced innovation and integrated digital tools achieved better service quality, efficiency, and citizen participation (â H” 0.5, p < 0.01). This was compared to the moderate effect of application usability and alignment (â H” 0.3, p < 0.05). Although user-friendly “Quick Win” apps improved services, their potential was limited by low organizational readiness and poor integration. Qualitative evidence confirmed that leadership support and staff empowerment were crucial to success. These findings demonstrate the importance of pairing technology with human capacity and collaborative governance. The study proposes a design framework that combines capacity building with application architecture refinements to institutionalize smart governance principles.